2002
DOI: 10.1111/j.1572-0241.2002.05691.x
|View full text |Cite
|
Sign up to set email alerts
|

GI distension in severe ulcerative colitis

Abstract: In severe UC, persistent GI distension characterized a subgroup of patients with poor response to medical therapy and at higher risk for TMC and of need for surgery. The development of MODS was the most important predicting factor for fatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
3
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 42 publications
2
24
3
3
Order By: Relevance
“…In a more recent prospective study toxic megacolon was reported in 7.9% of patients admitted with UC. 5 Until the late 1990s the incidence of toxic megacolon in patients with pseudomembranous colitis (PMC) was reported between 0.4% and 3%. [6][7][8] Over the last decade, however, major changes in the epidemiology of Clostridium difficile infections (CDI) have been observed.…”
Section: Epidemiologymentioning
confidence: 99%
“…In a more recent prospective study toxic megacolon was reported in 7.9% of patients admitted with UC. 5 Until the late 1990s the incidence of toxic megacolon in patients with pseudomembranous colitis (PMC) was reported between 0.4% and 3%. [6][7][8] Over the last decade, however, major changes in the epidemiology of Clostridium difficile infections (CDI) have been observed.…”
Section: Epidemiologymentioning
confidence: 99%
“…Eighty percent of all cases occur during the first 4 years after diagnosis, and the event is not necessarily correlated with the aggressiveness of the disease [32][33][34][35]. Other less common acute complications of Crohn's disease (especially that involving the colon) include toxic megacolon, which is present in 4.4-6.4 % of patients with colon involvement and is also an early event [36][37][38], and massive hemorrhage, with an incidence of around 1 %. In 15-20 % of patients with large intestinal…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…This phenomenon is now more widely known as multiple organ dysfunction syndrome (MODS) and it is considered to be related to the systemic inflammatory response syndrome (SIRS). Recent studies [5, 16] indicate that severe colitis must be included among the causes of MODS. In patients with UC, MODS is frequently preceded by TM and it is responsible for the majority of UC cases with a fatal outcome [16].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the associated high morbidity and mortality, early recognition and management of TM is of paramount importance [5]. The role of medical therapy of TM remains controversial both in infectious and IBD colitis.…”
Section: Introductionmentioning
confidence: 99%